Immunogenicity and Clinical Efficacy of Influenza Vaccination in Pregnancy - Kay, Alexander W.; Blish, Catherine A. (Frontiers in Immunology, 2015)
Pregnant women are at high risk from influenza due to disproportionate morbidity, mortality, and adverse pregnancy outcomes following infection. As such, they are classified as a high priority group for vaccination. However, changes in the maternal immune system required to accommodate the allogeneic fetus may alter the immunogenicity of influenza vaccines. A large number of studies have evaluated the safety of the influenza vaccine. Here, we will review available studies on the immunogenicity and efficacy of the influenza vaccine during pregnancy, focusing on both humoral and cellular immunity.